Geriatric nutritional risk index and newly developed scoring system as prognosis prediction for unresectable hepatocellular carcinoma patients treated with lenvatinib - Hideko Ohama; Atsushi Hiraoka; Toshifumi Tada; Masashi Hirooka; Kazuya Kariyama; Joji Tani; Masanori Atsukawa; Koichi Takaguchi; Ei Itobayashi; Shinya Fukunishi; Kunihiko Tsuji; Toru Ishikawa; et al. (Scientific Reports)
Abstract In the current era of immune therapy, lenvatinib (LEN) continues to be vital for treating unresectable hepatocellular carcinoma (uHCC) patients. This study investigates the importance of nutritional status in the prognosis of uHCC patients receiving LEN and evaluates a new prognostic scoring system that combines the geriatric nutritional risk index (GNRI) and systemic inflammatory response. From 2018 to 2022, 484 uHCC patients treated with LEN (384 males, median age 73). Prognostic value was compared between GNRI and C-reactive protein (CRP) scoring (GNRI-C score), GNRI, and neo-Glasgow prognostic score (neo-GPS). Evaluation was based on the Akaike information criterion (AIC) and concordance index(c-index). Median progression-free survival (mPFS) was 9.3/6.8/4.6 months for GNRI no-risk/low-risk/moderate-to-major risk (p < 0.01, AIC 4742.4/c-index 0.585). Median overall survival (mOS) was 27.8/15.2/9.5 months (p < 0.01, AIC 3433.34/c-index 0.639). For GNRI-C score, mPFS was 10.8/7.1/5.6/4.0 months (score 0/1/2/3) (p < 0.01, AIC 4732.82/c-index 0.6), while neo-GPS showed mPFS of 8.5/5.1/5.2 months (p < 0.01, AIC 4745.89/c-index 0.562). For mOS, GNRI-C score demonstrated 28.6/20.0/10.1/8.4 months (score 0/1/2/3) (p < 0.01, AIC 3420.27/c-index 0.652), while neo-GPS indicated 21.0/12.4/4.5 months (p < 0.01, AIC 3468.84/c-index 0.564). The newly devised GNRI-C score, incorporating nutritional and inflammatory markers, could offer improved prognostic predictions for uHCC patients treated with LEN.